Photocatalytic H2O2 Production over Ultrathin Layered Double Hydroxide with 3.92% Solar-to-H2O2 Efficiency - Xi, Yamin; Lu, Zechun; Bao, Tong; Zou, Yingying; Zhang, Chaoqi; Xia, Chunhong; Wei, Guangfeng; Yu, Chengzhong; Liu, Chao (Nano-Micro Letters, 2026)
Artificial photosynthesis of hydrogen peroxide (H2O2) from earth-abundant water and oxygen is a sustainable approach, however current photocatalysts suffer from low production rate and solar-to-chemical conversion efficiency (< 1.5%). Herein, we report that nickel–chromium layered double hydroxide with intercalated nitrate (NiCrOOH-NO3) and a thickness of 4.4 nm is an efficient photocatalyst, enabling a H2O2 production yield of 28.7 mmol g−1 h−1 under visible light irradiation with 3.92% solar-to-chemical conversion efficiency. Experimental and computational studies have revealed an inherent facet-dependent reduction–oxidation reaction behavior and spatial separation of photogenerated electrons and holes. An unexpected role of intercalated nitrate is demonstrated, which promotes excited electron—hole spatial separation and facilitates the electron transfer to oxygen intermediate via delocalization. This work provides understandings in the impact of nanostructure and anion in the design of advanced photocatalysts, paving the way toward practical synthesis of H2O2 using fully solar-driven renewable energy. Highlights: 1 The use of layered double hydroxides for photocatalytic for H2O2 production is innovatively demonstrated. 2 Facet-dependent spatial charge separation enables maximized carrier utilization efficiency. 3 The unique role of intercalated nitrate in promoting electron-hole separation and facilitating intermolecular electron transfer is unveiled. 4 A record-high H2O2 production rate of 28.7 mmol g-1 h-1 with 3.92% solar-to-chemical efficiency is achieved.